2013
DOI: 10.1155/2013/569564
|View full text |Cite
|
Sign up to set email alerts
|

Denervation as a Common Mechanism Underlying Different Pulmonary Vein Isolation Strategies for Paroxysmal Atrial Fibrillation: Evidenced by Heart Rate Variability after Ablation

Abstract: Backgrounds. Segmental and circumferential pulmonary vein isolations (SPVI and CPVI) have been demonstrated to be effective therapies for paroxysmal atrial fibrillation (PAF). PVI is well established as the endpoint of different ablation techniques, whereas it may not completely account for the long-term success. Methods. 181 drug-refractory symptomatic PAF patients were referred for segmental or circumferential PVI (SPVI = 67; CPVI = 114). Heart rate variability (HRV) was assessed before and after the final a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 26 publications
(33 reference statements)
1
24
1
Order By: Relevance
“…10 The absolute value of SDNN at 3 months after CPVI was previously identified as an independent risk factor for an AF relapse. 8 However, our study further underlines the utility of the periprocedural SDNN analysis. First, we show that the PAF patients with higher preablation SDNN (as a measure of overall HRV) are the best candidates for CPVI.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…10 The absolute value of SDNN at 3 months after CPVI was previously identified as an independent risk factor for an AF relapse. 8 However, our study further underlines the utility of the periprocedural SDNN analysis. First, we show that the PAF patients with higher preablation SDNN (as a measure of overall HRV) are the best candidates for CPVI.…”
Section: Resultsmentioning
confidence: 51%
“…Predicting circumferential pulmonary vein isolation outcome with the periprocedural assessment of changes in heart rate variability Previous studies identified changes in HRV occurring immediately after CPVI as a predictor of AF recurrence. 3,[6][7][8]12,13,15 Thus, postablation findings of high HF and a low LF / HF ratio or that changed by more than 0.26 were all independently associated with LRAF. 6,7 However, interpreting changes in the HRV frequency parameters (ie, HF and LF) is limited because their assessment depends considerably on respiration and measurement conditions.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The ablation of the ganglionated plexuses (GPs) was done in this aforementioned sequence in all patients. Each GP received at least 5 RF applications (30 s, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Watts according to the ablation site) with a mean RF time of 4.6±2.3 min. Next the sheath was withdrawn to the right atrium, a 20-polar hallo catheter was added, and an ablation of the cavotricuspid isthmus was performed.…”
Section: Hybrid Group-ep Partmentioning
confidence: 99%